La red social Facebook y su influencia como fuente de comunicación en los estudiantes de tercero de bachillerato de la Unidad Educativa Fiscomisional San Juan Bautista en el periodo mayo-julio 2022 - Vasco Martínez, Ana Cristina (2022)
Nowadays, social networks have become a major factor in society. Facebook is a platform that has allowed to maintain a relationship in real time. That is why, many educational institutions, use this medium to stay in touch with students. But there may be factors that affect the dissemination of content. Therefore, the main purpose of this research is to analyze the influence of the social network Facebook as a source of dissemination of communication among students in third year of high school of the Unidad Educativa Fiscomisional San Juan Bautista del canton Catamayo, in the period May-June 2022. IN this research work, the quantitative method was used. This allowed the extraction of information through observation matrices and mixed analytical surveys, with open and closed questions, which facilitated data collection. The results show that the level of interaction increases or decreases according to the type of publication. Videos with student participation have a higher reach compared to institutional reports. Therefore, the use of audiovisual content “videos” generates greater interest. In conclusion, there was a lack of planning, organization and consistency in the dissemination of institutional content that could be of interest to students. This shortcoming significantly exacerbates the lack of interest with identity and positioning of the page in the community of both teachers and students. Keywords: Social networks; interaction; students; Facebook; dissemination.